THE ANALYSIS OF MANAGEMENT OF INCLUSIVE EDUCATION AT SMPN 4 MOJOSONGO BOYOLALI - Ikang Maulana Mas’ud; Titik Djumiarti (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2021)
The inclusive education system is very wide open for children with special needs to be able to attend school and be in the same class with other children in the same school. This spirit is contained in The Act Number 20 of 2003 concerning the National Education System which ensures that children with special needs have access to education similar to other students. This study aims to analyze the management of inclusive education at SMPN 4 Mojosongo Boyolali using the management process according to Mee, namely planning, organizing, actuating, and controlling. The method used in this study is a descriptive qualitative method using informants from teachers or educators at SMPN 4 Mojosongo Boyolali. The results obtained indicate that the implementation of inclusive education has not yet been fully implemented, in the form of curriculum and teaching materials that are still equated with other students, the absence of special facilities and infrastructure for inclusive students, and the absence of a special supervisor teacher